Biogeographic patterns and environmental drivers of species richness in the globally distributed Millettioid/Phaseoloid clade (Fabaceae, subfamily Papilionoideae) - Oyebanji, Oyetola O.; Onditi, Kenneth O.; Azevedo, Josué A. R.; Rahaingoson, Fabien R.; Nneji, Lotanna M.; Adeleye, Matthew. A.; Stull, Gregory W.; Zhang, Rong; Yi, Ting-Shuang (Frontiers in Ecology and Evolution, 2023)
Introduction The Millettioid/Phaseoloid (MP) clade of Fabaceae is globally distributed, economically important, and highly diverse, making it an attractive system for studying biogeographic and macroecological patterns at a global scale. We conducted the first global macroecological study to map and explore the environmental drivers of the MP clade's species richness patterns. Methods We compiled 116,212 species occurrences (161 genera) for the MP clade and 20 environmental variables (19 bioclimatic variables and elevation). Geospatial analyses were performed to estimate species richness patterns and biogeographic heterogeneity. The effects of environmental variables on the species richness of the MP clade were measured through multiple regression models. Results Our study identified the megathermal regions as hotspots of species richness for the MP clade. While species distributions and richness largely fit the latitudinal diversity gradient pattern, there was a significant negative relationship between the species richness of the MP clade along the latitude and longitude. The Afrotropic biogeographic realm had the highest alpha diversity ( 36%); in terms of biome types, tropical and subtropical moist broadleaf forests had the highest alpha diversity (25%), while the beta diversity revealed a high dispersal rate and habitat tracking. Furthermore, the species richness was positively influenced by multiple climatic factors, with the mean diurnal range of temperatures and precipitation in the warmest quarter having strongest influence. Discussion Overall, the staggering species richness patterns could be explained by multiple diversity gradient hypotheses. Particularly, colder climates play a crucial role in shaping the species richness pattern by limiting the ecological opportunities for MP clade species in the higher latitudes of the Northern Hemisphere. This suggests that the species richness patterns of the MP clade can be described as "when dispersal meets adaptation." Our study provides a new basis for identifying priority regions for conservation of legumes.